2006
DOI: 10.1080/08035250600589041
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and overweight are associated with symptoms of gastro‐oesophageal reflux

Abstract: The prevalence of symptoms associated with gastro-oesophageal reflux was increased in children with asthma and in overweight children. Overweight and asthma were independently associated with GERD symptoms, and overweight did not explain the higher frequency of GERD in asthma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 29 publications
1
30
1
Order By: Relevance
“…Our study was the first to investigate EBC concentrations of calcium and magnesium in GERD patients, so we can only speculate on the physiologic function of these parameters. GERD symptoms are known to be possibly confused with acute asthma symptoms, thus leading to inappropriate therapeutic approach (22,25). In addition, GERD is present in approximately two-thirds of asthmatic children (48) and can contribute to asthma exacerbation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study was the first to investigate EBC concentrations of calcium and magnesium in GERD patients, so we can only speculate on the physiologic function of these parameters. GERD symptoms are known to be possibly confused with acute asthma symptoms, thus leading to inappropriate therapeutic approach (22,25). In addition, GERD is present in approximately two-thirds of asthmatic children (48) and can contribute to asthma exacerbation.…”
Section: Discussionmentioning
confidence: 99%
“…Asthma was chosen for the presence of bronchoconstriction, and GERD because the symptoms may occasionally be erroneously attributed to asthma, thus leading to inappropriate therapeutic approach (22,25).…”
Section: Introductionmentioning
confidence: 99%
“…A populationbased birth cohort showed that the association between reflux symptoms and respiratory symptoms in young adults was independent of BMI [113]. Overweight did not explain the higher frequency of GERD in asthma patients [114].…”
Section: Gastro-oesophageal Refluxmentioning
confidence: 99%
“…In a recent study by Khoshoo and Haydel Jr [15], 44 children (8-15 years old) with asthma and GERD had a significantly beneficial effect in preventing an exacerbation of asthma after a combination therapy of esomeprazole and metoclopramide. In a Norwegian study of 872 children from 7 to 16 years of age, Stordal et al [16] found that GERD occurred in 19.7% of asthmatic patients, compared with 8.5% of healthy controls. Also in the same study, overweight children had a positive GERD symptom score more frequently than children with normal weight (25.4% vs 16.2%; unadjusted OR, 1.8; 95% CI, 1.2-2.6, P = 0.004) [16].…”
Section: Clinical Manifestations Of Gerd In Children and Adolescentsmentioning
confidence: 97%